Education Keeping the Machinery in Computing Education. - Connor, Richard; Cutts, Quintin; Robertson, Judy (Communications of the ACM, 2017)
The authors discusses their experiences in developing a computer science (CS) education curriculum in Scotland for students aged three to 15, particularly the incorporation of intellectual and developmental aspects of computational mechanisms in the curriculum. According to the authors, the curriculum is based on a three-point base that incorporates an understanding of computational mechanism domains, the domains themselves, and how to utilize computational mechanisms to model parts of the domains.